ASSESSMENT OF CYTOTOXICITY, ANTIOXIDANT AND ANTIMICROBIAL PROPERTIES OF THE LEAF EXTRACTS OF ABELMOSCHUS ESCULENTUS CULTIVATED IN NORTHERN NIGERIA: LEAF EXTRACTS OF ABELMOSCHUS ESCULENTUS - Danjuma, Kabir; Abdu, Kabir; Lawan, Imrana; Amayandi, Magaji; Jibrin, Moses (STIKes Mandala Waluya Kendari, 2024)
Background: Okra (Abelmochus esculentus) belongs to Malvaceae family and is widely cultivated in Africa, India, America, and Brazil for its fibrous fruits containing round, white seeds. This study was carried out to assess the cytotoxicity, antioxidant and antimicrobial activities of the leaf extracts of Abelmoschus esculentus cultivated in north-western, Nigeria. Methods: The plant sample was collected, washed, identified, grounded into powder and extracted using solvent extractor with ethanol as solvent, and this was followed by fractionation using three more solvents of different polarities (starting with n-hexane, ethyl acetate, and then methanol). The cytotoxicity of the extracts was assessed using Brine Shrimp Lethality assay; Antioxidant activity of the extracts was studied using DPPH radical scavenging assay method, while antimicrobial activity was determined using agar well diffusion method. Results: The cytotoxicity results showed n-hexane having highest activity (LC50 394.499 µg/ml), followed by methanol extract (LC50 538.098 µg/ml), ethyl acetate extract (LC50 2106.499 µg/ml), and then crude extract (LC50 5634.091 µg/ml) respectively. The results also revealed that the extracts possessed significant antioxidant activity, with crude extract showing highest activity (IC50 = 74.229 µg/ml), followed by methanol extract (IC50 = 83.396 µg/ml), ethyl acetate extract (IC50 = 126.159 µg/ml), and then n-hexane extract (IC50 = 138.936 µg/ml). The extracts revealed remarkable antimicrobial activity and were even more noticeable in antibacterial result at higher concentrations with ethyl acetate extract showing largest zone of inhibitions, followed by n-hexane extract, crude extract, and then methanol extract respectively. Conclusion: From the findings of this research study we have concluded that the leaf extracts Abelmoschus esculentus possesses antimicrobial and antioxidant activities and is also less toxic.